Graphene films irradiated with safe low-power NIR-emitting diodes kill multidrug resistant bacteria. (15th August 2021) - Henriques, Patrícia C.; Pereira, Andreia T.; Bogas, Diana; Fernandes, José R.; Pinto, Artur M.; Magalhães, Fernão D.; Gonçalves, Inês C.
Abstract: Bacterial adhesion to surfaces is the onset of biofilm formation and a hard problem to tackle, aggravated by the rise in drug-resistant bacteria, responsible for more than 500 000 deaths globally/year. This work reports few-layer graphene (FLG) and few-layer graphene oxide (FLGO) as stand-alone light-responsive platforms to develop smart antibacterial surfaces. Films exposure to low-intensity NIR drastically improve their ability to kill planktonic (up to ∼99%) and adherent (up to ∼85%) methicillin-resistant S. aureus and S. epidermidis . Upon irradiation, a mild photothermal effect is observed in supernatant, with temperature rising from 37.0 °C to 39.0 °C–42.0 °C, while surface temperature of non-oxidized FLG films increases to 51.3 °C versus 56.0 °C for oxidized films. Both films prompt total glutathione oxidation when irradiated, despite FLG films induce higher ROS generation than FLGO, suggesting antioxidants depletion occurs preferentially by ROS-dependent pathway (photodynamic effect) for FLG versus ROS-independent pathway for FLGO films. This proof-of-principle study demonstrates that safe, low-intensity NIR irradiation is a valuable and effective tool to boost graphene surfaces' antibacterial performance through a synergistic photothermal and photodynamic effect. These stand-alone NIR-activated graphene-based platforms arise as simple and economical disinfection surfaces/systems, with widespread use in medical and non-medical applications. Graphical abstract: Image 1 Highlights: Graphene films irradiated with low-power (0.15 W/cm 2 ) NIR (812 nm) have bactericidal action. Oxidized films (FLGO) have higher bactericidal performance than non-oxidized (FLG). NIR-irradiated FLGO films kill ∼99% planktonic bacteria (MRSA and S. epidermidis ). Antibacterial performance occurs through synergistic PTT and PDT effects. FLG acts mainly by ROS-dependent and FLGO by ROS-independent pathways.